OPTIMIZATION OF ONLINE LEARNING DURING THE PANDEMIC IN THE NORTH SUMATRA REGION - Sakinah Siregar; Masyunita Siregar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The purpose of this study was to describe the optimization efforts carried out by teachers, especially teachers at the early childhood level during the pandemic Covid-19. This research was conducted using a qualitative method, using a questionnaire distributed online via google form. The sample of this study was early childhood teachers spread across various regions in the province of North Sumatra. The results of the study show that teachers in general optimize through the use of technology media, develop self-efficacy in dealing with pandemic conditions and involve parents in the online learning process. This is evidenced from 15 research indicators. Starting from doing online learning, using learning media through zoom meetings or whatsapp groups, creating virtual learning media, make video tutorials, digital exploration in online learning, join webinars for self-improvement during the pandemic, communicative in the implementation of online learning, involve parents in online learning, provide simulation and socialization of learning models that need to be done so that parents are ready to run it, learning activities for children and parents sent via video, giving daily learning plan to parents as a reference for children's online learning from home, aspects of child development are measured through the tasks given, visiting the child's house to see the child's progress, children's tasks are adjusted to the needs of children during the pandemic, provide questionnaires to parents to participate in assessing child development.